Day 3 Thu, February 27, 2014 2014
DOI: 10.2118/167768-ms
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Assessment of World Recoverable Shale Gas Resources

Abstract: Many shales previously thought of as only source rocks are now recognized as self-sourcing reservoirs that contain large volumes of natural gas and liquid hydrocarbons that can be produced using horizontal drilling and hydraulic fracturing. However, shale gas resources and development economics are uncertain, and these uncertainties beg for a probabilistic solution. Our objective was to probabilistically determine the distribution of technically recoverable resources (TRR) and shale original gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…We used one probability density function (pdf) for oil condensate recovery and one for gas recovery (Figure 10), as applicable to a wet gas product range in various ratios weighed by the GOR. The conventional curves were based on conference data compiled by Laherrere [51], which were previously used to argue unconventional resources may have similar distributions-but shifted toward the left in the plot of cumulative recovery probabilities [44,45]. We found that the conventional oil recovery factors fit well to a normal distribution, with a mean at 28% and standard deviation of about 14%.…”
Section: Recovery Factormentioning
confidence: 78%
“…We used one probability density function (pdf) for oil condensate recovery and one for gas recovery (Figure 10), as applicable to a wet gas product range in various ratios weighed by the GOR. The conventional curves were based on conference data compiled by Laherrere [51], which were previously used to argue unconventional resources may have similar distributions-but shifted toward the left in the plot of cumulative recovery probabilities [44,45]. We found that the conventional oil recovery factors fit well to a normal distribution, with a mean at 28% and standard deviation of about 14%.…”
Section: Recovery Factormentioning
confidence: 78%
“…A foreign formation similar to a Colombian formation must be identified in this case, aimed at correlating the physic chemical features of the flowback. According to data as shown in Dong et al (2014), Lesar (2011), U.S. Energy Information Administration (2011), Murphy (2013) formation located in the Magdalena Valley (VMM) and the Shale Eagle Ford, showed similarities in their petro physic and geologic features; as shown in Table 2. In order to establish the similarities between these two formations the following parameters were taken into account: permeability, porosity, TOC (Cerón,, Walls & Diaz, 2013), type of hydrocarbons, type of kerogene, temperature and vitrinite reflectance (Ro).…”
Section: Characterization Of the Flowback Using An Analogous Field In Usamentioning
confidence: 99%
“…Source:(Dong et al, 2014;Lesar, 2011; U.S. Energy Information Administration, 2011;Murphy, 2013). Formation data of La Luna shown in the Table, is the result of the comprehensive characterization of the bottom interval laboratory in La Luna well in theICP, 2012 …”
mentioning
confidence: 99%
“…Input parameters for the base reservoir model (modified from[16,17,[19][20][21][22][23][24][25][26]). …”
mentioning
confidence: 99%